Diferencirano cestninjenje tovornih vozil in drugi instrumenti učinkovitejše cenovne in prometne politike na transportnem trgu v Sloveniji - Matajič, Mateja (IB revija (Ljubljana), 2013)
We developed a panel data econometric model for road freight transport demand on the 10 toll road sections in Slovenia, which is the first of its kind in Slovenia. Freight transport demand on Slovenian motorways is price-inelastic. Increasing prices for the use of toll roads in Slovenia could provide more financial resources to the motorway operator. Validated different price elasticities of transport demand suggest the introduction of differentiated tolls, which allows simultaneous pursuit of the objectives of financial sustainability, cost prices and a higher level of internalisation of the external costs of transport. Responsiveness of transport demand with respect to fuel prices points towards managing transport demand with different levels of fuel prices. The elasticity of freight transport demand in Slovenia could be increased by the expansion of transport supply and by investment in the development of competitiveness of alternative rail transport as well as of alternative transport routes.
Keywords: cestni transport; ekonometrija; ekonometrični modeli; cestninjenje; cestna infrastruktura; prometna politika; Slovenia; Slovenija